PENGARUH POLA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Perusahaan Umum Bulog Kabupaten Sumbawa) - S Syafruddin; Maria Rosari Wonga (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
The purpose of this study was to determine the effect of leadership patterns on employee performance at Bulog Public Company, Sumbawa Regency. The number of employees at Bulog Public Company, Sumbawa District is 24 people, so this study uses a saturated sample (census sampling). The type of data in this study is quantitative data obtained from primary sources. Data was collected by using a questionnaire method. The data analysis technique used simple linear regression analysis, individual parameter hypothesis testing (t test) and coefficient of determination test (R2). The results of this study showed that the pattern of leadership has a positive and significant effect on employee performance at Bulog Public Company, Sumbawa District. It was obtained from the results of simple linear regression coefficient testing, namely the tcount value is greater than the ttable value (2.386>2.074), and the significant value of the calculation result is less than = 5% (0.029<0.05). In the R2 test, the value of Adjusted R Square is 0.700, meaning that the leadership pattern contributes to changes in employee performance at Bulog Public Company, Sumbawa District, by 70%, while the remaining 30% is influenced by other factors outside this research.